Cloning and functional analysis of three aphid alarm pheromone genes from German chamomile (Matricaria chamomilla L.). (May 2020) - Ling, Chengcheng; Zheng, Lujie; Yu, Xiaorui; Wang, Huanhuan; Wang, Chengxiang; Wu, Haiyan; Zhang, Jie; Yao, Ping; Tai, Yuling; Yuan, Yi
Highlights: Establishment of a German chamomile hairy root transformation system. Cloning and expression analysis of three sesquiterpene synthase genes. In vitro and in vivo enzyme activity of three sesquiterpene synthases. Abstract: German chamomile ( Matricaria chamomilla L.) is one of the most ancient medicinal species in the world and terpenoids from their flowers have important medicinal value. We cloned three sesquiterpene synthase genes, McGDS1, McGDS2 and McGDS3, and performed sequence alignment and phylogenetic analysis. The encoded proteins possess three conserved structural features: an RRxxxxxxxxW motif, an RxR motif, and a DDxxD motif. McGDS1, McGDS2 and McGDS3 were confirmed to be (E)-farnesene synthase, germacrene D synthase, and germacrene A synthase, respectively. Subcellular localization revealed diffuse GFP reporter-gene signals in the cytoplasm and nucleus. qPCR indicated that McGDS1, McGDS2 and McGDS3, were more highly expressed in young flowers than in old flowers and the expression was highly correlated with amounts of the end-product essential oils ((E)-β-farnesene, germacrene D and β-elemene), with coefficients of 0.76, 0.83 and 0.68, respectively. We also established a transformation system for chamomile hairy roots. The overexpression of McGDS1, McGDS2 and McGDS3 resulted in γ-muurolene accumulation in hairy roots. The activity of three aphid alarm pheromones here forms the molecular basis for the study of the biosynthesis and regulation of volatile terpenes. Transformation of chamomile hairy roots provides a simple system in which to study terpene biosynthesis in chamomile.